Labour Relations in the Public Service : Manitoba - Woods, H. D. (Relations industrielles / Industrial Relations, 1975)
In reference with the Manitoba Labour-Management Review Committee, the author deals with the problem of public employment labour relations and the use of the Review Committee as a device to explore a major public policy problem in industrial relations.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z